Bacterial Populations Colonizing and Degrading Rice Straw in Anoxic Paddy Soil - Weber, Sabine (American Society for Microbiology, 2001)
Rice straw is a major substrate for the production of methane, a greenhouse gas, in flooded rice fields. The bacterial community degrading rice straw under anoxic conditions was investigated with molecular methods. Rice straw was incubated in paddy soil anaerobically for 71 days. Denaturing gradient gel electrophoresis (DGGE) of the amplified bacterial 16S rRNA genes showed that the composition of the bacterial community changed during the first 15 days but then was stable until the end of incubation. Fifteen DGGE bands with different signal intensities were excised, cloned, and sequenced. In addition, DNA was extracted from straw incubated for 1 and 29 days and the bacterial 16S rRNA genes were amplified and cloned. From these clone libraries 16 clones with different electrophoretic mobilities on a DGGE gel were sequenced. From a total of 31 clones, 20 belonged to different phylogenetic clusters of the clostridia, i.e., clostridial clusters I (14 clones), III (1 clone), IV (1 clone), and XIVa (4 clones). One clone fell also within the clostridia but could not be affiliated to one of the clostridial clusters. Ten clones grouped closely with the genera Bacillus (3 clones), Nitrosospira (1 clone), Fluoribacter (1 clones), and Acidobacterium (2 clones) and with clone sequences previously obtained from rice field soil (3 clones). The relative abundances of various phylogenetic groups in the rice straw-colonizing community were determined by fluorescence in situ hybridization (FISH). Bacteria were detached from the incubated rice straw with an efficiency of about 80 to 90%, as determined by dot blot hybridization of 16S rRNA in extract and residue. The number of active (i.e., a sufficient number of ribosomes) Bacteria detected with a general eubacterial probe (Eub338) after 8 days of incubation was 61% of the total cell counts. This percentage decreased to 17% after 29 days of incubation. Most (55%) of the active cells on day 8 belonged to the genus Clostridium, mainly to clostridial clusters I (24%), III (6%), and XIVa (24%). An additional 5% belonged to the Cytophaga-Flavobacterium cluster of the Cytophaga-Flavobacterium-Bacteroides phylum, 4% belonged to the α, β, and γ Proteobacteria, and 1.3% belonged to the Bacillus subbranch of the gram-positive bacteria with a low G+C content. The results show that the bacterial community colonizing and decomposing rice straw developed during the first 15 days of incubation and was dominated by members of different clostridial clusters, especially clusters I, III, and XIVa.